Confronting the mismatch between problems and solutions: Global social policy in an era of state skepticism and multilateral retrenchment - Martínez Franzoni, Juliana (2025)
From 1945 to the mid-1980s, ‘embedded liberalism’ (Ruggie, 1985) combined free trade with capital controls, fixed exchange rates, and welfare states, balancing openness with national economic protection and sociopolitical stability. This multilateral order began to erode after the United States left the gold standard in the 1970s and capital controls collapsed, paving the way to ‘disembedded liberalism’ and a vicious circle where global markets undermined nation-state democracies. Since the 1990s, three competing visions emerged: defenders of neoliberal globalization, nationalist de-globalizers seeking ‘sovereign’ economies, and advocates of the new global social contract with binding regulation and taxation—namely a form of global social democracy. Today’s ‘new transnational right’ drives nationalist deglobalization, resulting in an unstable and unsustainable combination of unrestrained global markets and rising authoritarian nationalism. Strong global and national social policies could counter this trend, but pathways remain unclear.